Feature Paper in Antibiotics for 2019 - Lipman, Jeffrey (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There has been much speculation about a possible antibiotic Armageddon; this would be the result of having untreatable post-operative infections, and similarly untreatable complications after chemotherapy. The now famous "O'Neill Report" (https://amr-review.org/) suggests that more people could die from resistant bacterial infections by 2050 than from cancer. We are still learning about all the subtle drivers of antibiotic resistance, and realizing that we need a single "whole of health" co-ordinated policy. We ingest what we sometimes feed to animals. There do not seem to be any new classes of antibiotics on our horizon. Perhaps something that has been around "forever" will come to our rescue-bacteriophages! Nevertheless, we have to do things differently, use antibiotics appropriately, for the correct indication, for the correct duration and with the correct dose, and with that, practice good antibiotic stewardship. Whilst by no means comprehensive, this book does cover some of the many topics of antibiotic stewardship. It also addresses some of the older antibiotics, some new combinations, and even some new agents. Last, and by no means least, there are two excellent articles on bacteriophages.